Answer:
[tex]c =2 \sqrt{3}[/tex]
Step-by-step explanation:
Using Mean Value Theorem for integrals
[tex]\int^b_a \ f(x) \ dx = f(c) (b-a)[/tex]
[tex]f(x) = y = \dfrac{x^2}{4}, [0,6][/tex]
Hence;
[tex]\int^b_a \ f(x) \ dx = f(c) (b-a)= \int^6_0 \dfrac{x^2}{4}dx = f(c) (6-0)[/tex]
From above, using the power rule for integration
Then;
[tex]\int x^n dx = \dfrac{x^{n+1}}{x+1}+C[/tex]
Thus;
[tex]f(c)(6) = \Big[ \dfrac{x^3}{3(4)} \Big]^6_0[/tex]
[tex]6f(c) =\Big[ \dfrac{x^3}{12} \Big]^6_0 = (\dfrac{6^3}{12}-0)[/tex]
[tex]6f(c) = (18-0)[/tex]
[tex]6f(c) = (18)[/tex]
[tex]f(c) = 3[/tex]
From;
[tex]f(x) = \dfrac{x^2}{4} \implies f(c) = \dfrac{c^2}{4}[/tex]
Hence,
[tex]\dfrac{c^2}{4}= 3[/tex]
[tex]c^2 =12[/tex]
[tex]c = \sqrt{12}[/tex]
[tex]c = \sqrt{4 \times 3}[/tex]
[tex]c =2 \sqrt{3}[/tex]